Kepemimpinan Strategis dalam Peperangan Asimetris (Studi Kasus: Kepemimpinan Strategis Zulkifli Lubis pada Operasi Militer Aceh) - Kartika P, Seri Nenni; Priyanto, Priyanto; Afifuddin, M (Universitas Pahlawan Tuanku Tambusai, 2025)
Around the year 1990, armed conflict in Aceh began to escalate with the emergence of the Free Aceh Movement (GAM). This conflict occurred in Aceh, a province of Indonesia, in response to the independence demands put forth by GAM. The background of the conflict includes the dissatisfaction of the Acehnese people with the central government, which was perceived as unjust in the distribution of resources and governance. This prolonged tension led to the necessity for military intervention to restore stability and security in the region. Zulkifli Lubis, serving as the Chief of Operations, implemented innovative and adaptive military strategies to address the challenges of asymmetric warfare. His approach involved the utilisation of robust intelligence and support from the local community to achieve military objectives. By leveraging accurate information and fostering relationships with the populace, Lubis successfully alleviated tensions in Aceh. This research aims to analyse the impact of Zulkifli Lubis's strategic leadership in the context of the Aceh conflict and its relevance to future military operations. The objective of this study is to understand how strategic leadership can influence the outcomes of military operations within the framework of asymmetric warfare. The theoretical framework employed in this research encompasses theories of strategic leadership and innovation in warfare strategy. There are three research questions, beginning with how Zulkifli Lubis's leadership strategy affected the dynamics of the conflict in Aceh. The subsequent question addresses the approaches taken by Lubis in integrating intelligence and community support. The third question explores how the innovations in warfare strategy implemented by Lubis contributed to the success of military operations. The findings of the research indicate that Zulkifli Lubis's strategic leadership had a significant impact on diminishing the strength of GAM and restoring government control in Aceh. Additionally, the study reveals that the approaches adopted by Lubis can serve as a model for military operations in other conflict-affected regions.